HASRAT KEPRIBADIAN TOKOH UTAMA DALAM CERPEN SAMURAI KARYA KUNTOWIJOYO: KAJIAN PSIKOANALISIS JACQUES LACAN - Dina Amalia; Selvi Ramah Hadi; Elsa Wulandari (SeBaSa)
This study aims to describe (1) the form of Real and Imaginary Personality Desire of the Main Character in Samurai Short Stories by Kuntowijoyo, including the dynamics of husband-wife relationships that are trapped in conflict due to differences in social backgrounds and conflicting expectations; (2) patriakal norms and gender injustice in the household. This research uses data in the form of words, phrases, sentences, and expressions from the short story Samurai by Kuntowijoyo, which is the main object of analysis. The results of this research are as follows. (1) The Real and Imaginary Personality Desires of the Main Character in Samurai Short Story by Kuntowijoyo: (a) the failure of Arif in soothing the crying of adults; (b) the failure of Arif to maintain control over his wife in the household; (c) the failure of Arif to accept the power of women in the household; (d) the failure of Arif to control his wife in the household; (e) the inability of Arif to control or understand his wife as a more rational individual and not trapped in traditional views of gender roles.